Obestatin regulates cardiovascular function and promotes cardioprotection through the nitric oxide pathway. Issue 12 (26th July 2017) - Penna, Claudia; Tullio, Francesca; Femminò, Saveria; Rocca, Carmine; Angelone, Tommaso; Cerra, Maria C.; Gallo, Maria Pia; Gesmundo, Iacopo; Fanciulli, Alessandro; Brizzi, Maria Felice; Pagliaro, Pasquale; Alloatti, Giuseppe; et al.
Abstract: Patients with ischaemic heart disease or chronic heart failure show altered levels of obestatin, suggesting a role for this peptide in human heart function. We have previously demonstrated that GH secretagogues and the ghrelin gene‐derived peptides, including obestatin, exert cardiovascular effects by modulating cardiac inotropism and vascular tone, and reducing cell death and contractile dysfunction in hearts subjected to ischaemia/reperfusion (I/R), through the Akt/nitric oxide (NO) pathway. However, the mechanisms underlying the cardiac actions of obestatin remain largely unknown. Thus, we suggested that obestatin‐induced activation of PI3K/Akt/NO and PKG signalling is implicated in protection of the myocardium when challenged by adrenergic, endothelinergic or I/R stress. We show that obestatin exerts an inhibitory tone on the performance of rat papillary muscle in both basal conditions and under β‐adrenergic overstimulation, through endothelial‐dependent NO/cGMP/PKG signalling. This pathway was also involved in the vasodilator effect of the peptide, used both alone and under stress induced by endothelin‐1. Moreover, when infused during early reperfusion, obestatin reduced infarct size in isolated I/R rat hearts, through an NO/PKG pathway, comprising ROS/PKC signalling, and converging on mitochondrial ATP‐sensitive potassium [mitoK(ATP)] channels. Overall, our results suggest that obestatin regulates cardiovascular function in stress conditions and induces cardioprotection by mechanisms dependent on activation of an NO/soluble guanylate cyclase (sGC)/PKG pathway. In fact, obestatin counteracts exaggerated β‐adrenergic and endothelin‐1 activity, relevant factors in heart failure, suggesting multiple positive effects of the peptide, including the lowering of cardiac afterload, thus representing a potential candidate in pharmacological post‐conditioning.